'After the very rare original': artist and antiquary the Revd John Brand. (29th January 2018) - Wood, Sileas
Abstract: During the closing years of the eighteenth century, minister and antiquary the Revd John Brand (1744–1806) undertook an extraordinary project of creating facsimile drawn copies of rare prints, with which to illustrate James Granger's Biographical History of England. Between 1790 and 1800 Brand personally created over 400 drawn copies of portrait prints which can be identified through his own annotations, a manuscript catalogue, and the catalogue of his posthumous sale. This paper will examine Brand's surviving works, his processes and the ways in which his drawings were shaped by his status as an antiquary, amateur artist, and print collector.